(untitled) (Web of Teachers: Inderscience Research, 2025)
Nationwide sports programs, the development of physical education and sports, as well as a number of other factors, have helped to increase the interest of the Chinese people in leading a healthy lifestyle. Bushubha is associated with achieving a high level of development of professional sports and sports journalism in general. Chinese athletes do not cease to be delighted with their victories in various sports, thanks to which the number of fans of interest in sports and sports journalism is growing in this country. In ancient times in China, sports such as horse racing, shooting, Football, Belt and ushu were popular. Various games and competitions played an important role in the life of the Chinese during celebrations and celebrations.